Практическая психология для подростков, или Как найти свое место в жизни - Снайдер Ди (АСТ-Пресс, 2000)
Экземпляры: ф.24 (20180115) / Инвентарный номер: 36242 / Цена: 36.50 / Авт.знак: С 53 / ГРНТИ: 15 / ББК: 88.8